Clearance profile of radioactive gold nanoparticle (198Au) conjugates-poliamidoamin generation 4-nimotuzumab ; potential radio-pharmaceutical theranostic agent - Halid, Nurhatidjah Awaliyah; Mutalib, Abdul; Pujiyanto, Anung; Gunawan, Adang Hardi (Universitas Ahmad Dahlan, 2017)
Theranostic agents are agents that combine diagnostic and therapeutic capabilities into a single agent. The presence of conjugated cancer which is therapeutic agents such as nimotuzumab monoclonal antibodies with radioactive gold nanoparticles stabilized with Polyamidoamine Generation 4 (PAMAM G4) dendrimer can actively interact with specific cancer cells. Radioactive gold (198Au) as a radiation transmitter Î² (961 keV) capable for killing cancer cells and (412 keV) Î³ rays that give a golden image in the body, thus acting as a theranostic agent. The purpose of this study was to obtain confident results of conjugate safety by observing the constituent clearance of 198AuNP-PAMAM G4-Nimotuzumab. The result of the conjugate clearance will be the reference for the metabolic state as a new, stable and complete radiofarmaka upon reaching the desired target. This study began with the synthesis of the conjugate of 198AuNp-PAMAM G4-nimotuzumab and then tested the clirens and analyzed the results of urine and mouse feces that had been injected with conjugate. Total clearance was obtained about 47.38% of the 198AuNP-PAMAM G4-Nimotuzumab conjugates that have been excreted through urine (18.26%) and stool (29.11%.). Urine and feces were analyzed with SDS-PAGE giving the spot above the 150 kDa band and showing the conjugate molecular weight. FTIR analysis of urine and feces by showing aldehyde functional groups (C = O), alcoholic groups (O-H), amine groups (C-N), and amine groups (N-H) indicating the presence of AuNP-PAMAM G4-Nimotuzumab conjugates in urine and mouse feces. The results of urine and fecal excretion of the conjugate are still conjugate-shaped supported by SDS PAGE analysis, UV-Vis spectrophotometer absorption analysis and functional group analysis with FTIR that has been conducted.